SISTEM INFORMASI KEUANGAN UNTUK MENINGKATKAN KINERJA UMKM - Agus Joko Waluyo; Sri Yunan Budiarsi (Universitas Trunojoyo Madura, 2016)
Micro, small and medium enterprises (SMEs) face the competitive conditions that demand the use of management information systems in support of competitive strategy, so as to compete with other companies. This study was to investigate the impact of information systems management, especially financial information manufacturing SMEs in Surabaya and Sidoarjo. This research is an action research, data used primary and secondary data obtained through surveys and interviews with SME owners followed by focus group to explore the information system needs of the data keuangan.Berdasar Department of Cooperatives and SMEs Surabaya East Java there are 133 SMEs and 28 SME Sidoarjo, have only SMEs manufacturing (processing raw materials into finished goods) that there are 73 (seventy three) eligible SMEs surveyed and just 14 (fourteen) SME owners who are willing to be surveyed and interviewed, to sharpen the results of a survey conducted focus group was attended by 11 owners of SMEs. The results of the survey and focus group showed that all respondents understand the importance of recording financial statements for the smooth running of the business, but in practice it does not keep records of financial, obstacles often faced is less memgerti in financial records so that only records the sale and the daily spending, while financial records another, are not done. Based on the real conditions, activities of training and personal mentoring on recording simple financial statements (with the help of MS Excel program).